Phosphorus and Nitrogen Drive the Seasonal Dynamics of Bacterial Communities in Pinus Forest Rhizospheric Soil of the Qinling Mountains - Wang, Hai H.; Chu, Hong L.; Dou, Qing; Xie, Qing Z.; Tang, Ming; Sung, Chang K.; Wang, Chun Y. (Frontiers in Microbiology, 2018)
The temporal distribution patterns of bacterial communities, as an important group in mountain soil, are affected by various environmental factors. To improve knowledge regarding the successional seasonal dynamics of the mountain soil bacterial communities, the rhizonsheric soil of a 30-year-old natural secondary Pinus tabulaeformis forest, located in the high-altitude (1900 m a.s.l.) of the temperate Qinling Mountains, was sampled and studied during four different seasons. The bacterial community composition and structure in the rhizonsheric soil were studied using an Illumina MiSeq Sequencing platform. Furthermore, the edaphic properties and soil enzymatic activities (urease, phosphatase and catalase) were measured in order to identify the main impact factors on the soil bacterial community. According to the results, all of the edaphic properties and soil enzymatic activities were significantly affected by the seasonal changes, except for the C/N ratio. Although the biomasses of soil bacterial communities increased during the summer and autumn (warm season), their Shannon diversity and Pielou’s evenness were decreased. Proteobacteria, Acidobacteria, Actinobacteria, Planctomycetes and Bacteroidetes were the predominant bacterial groups in all of the soil samples, and the genera of Ktedonodacter, Sphingobium as well as an unclassified member of the Ktedonobacteria were the keystone taxa. The composition and structure of soil baterial communities were strongly impacted by the edaphic properties, especially the temperature, moisture, ammoniacal nitrogen, available phosphorus and total phosphorus which were the crucial factors to drive the temporal distribution of the soil bacterial community and diversity. In conclusion, the soil temperature, moisture and the nutrients N and P were the crucial edaphic factors for shaping the rhizonsheric soil bacterial communities as season and climate change in a P. tabulaeformis forest of Qinling Mountains.